Shortening the Return-to-Play Times in Elite Athletes With Unstable Isolated Lisfranc Ligament Injuries Using a Knotless Interosseous Suture Button: Case Series and Literature Review. Issue 6 (17th June 2022) - Sullivan, Martin; Peckston, Dane; Alpuerto, Bernardino
Background: Isolated unstable Lisfranc ligament injuries in elite athletes are associated with a lengthy period of rehabilitation and prolonged absence from competition. Purpose: To assess the efficacy of a knotless, interosseous suture button system for repairing isolated unstable ligamentous Lisfranc injuries and its capacity to allow accelerated rehabilitation with earlier weightbearing and return-to-play times in elite athletes. Study Design: Case series; Level of evidence, 4. Methods: The authors retrospectively reviewed data from a prospectively compiled database for elite athletes treated by a single surgeon. All included patients had clinical and magnetic resonance imaging evidence of an unstable isolated complete ligamentous Lisfranc injury requiring surgical reduction and stabilization. All patients underwent surgery using a knotless interosseous suture button to achieve stabilization, followed by a standardized postoperative regimen involving full weightbearing at 4 weeks, and all had a minimum postoperative follow-up of 2 years. Results: Included were 12 patients: 7 National Rugby League (NRL) players, 2 professional dancers, 1 Olympic gymnast, 1 professional wakeboarder, and 1 professional NRL referee. The mean age of the patients was 21.1 years (range, 16-34 years). Ten patients underwent acute surgical stabilization within 3 weeks of the injury, and 2 patients sustained chronic isolated Lisfranc instability that was initially treated nonoperatively. All athletes were able to return to full weightbearing by 4 weeks postoperatively, successfully returned to training by 9 to 12 weeks, and returned to full competition by 12 to 16 weeks. No major complications were reported. Conclusion: Knotless interosseous suture button stabilization was a reliable treatment option for both acute and chronic isolated ligamentous Lisfranc injuries in these elite athletes. This technique does not require hardware removal, allows early weightbearing with accelerated rehabilitation, and may shorten the return-to-play interval.